2011
DOI: 10.1186/1472-6785-11-20
|View full text |Cite
|
Sign up to set email alerts
|

Population distribution models: species distributions are better modeled using biologically relevant data partitions

Abstract: BackgroundPredicting the geographic distribution of widespread species through modeling is problematic for several reasons including high rates of omission errors. One potential source of error for modeling widespread species is that subspecies and/or races of species are frequently pooled for analyses, which may mask biologically relevant spatial variation within the distribution of a single widespread species. We contrast a presence-only maximum entropy model for the widely distributed oldfield mouse (Peromy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 38 publications
0
43
1
Order By: Relevance
“…5), with a strong under-estimation of high probability values. We argue that these results are due to the spatially clustered distribution of targeted group presences used as pseudoabsences, leading to spatially autocorrelated background samples resulting in inflated AUC values (Gonzàlez et al, 2011), and also to an over-estimated suitability for a large proportion of non-sampled areas (Figs. 6 and 7), as compared to the other methods.…”
Section: Tg Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…5), with a strong under-estimation of high probability values. We argue that these results are due to the spatially clustered distribution of targeted group presences used as pseudoabsences, leading to spatially autocorrelated background samples resulting in inflated AUC values (Gonzàlez et al, 2011), and also to an over-estimated suitability for a large proportion of non-sampled areas (Figs. 6 and 7), as compared to the other methods.…”
Section: Tg Methodsmentioning
confidence: 97%
“…With this regard, Hernández et al (2006) suggested that research in environmental niche modelling should focus on broad distributional subunits based on distinct genetic linages. For instance, Gonzàlez et al (2011) demonstrated that omission error is reduced when "biologically meaningful" data (in reference to genetically distinct populations of the same species) are modelled. Hence, in this study we consider genetically differenced groups of Quercus sp.…”
Section: Species Datamentioning
confidence: 99%
“…This method has been used for species occurring over a large distribution range and extended environmental gradients [44], [51], [71]. We split our biased datasets in a northern and a southern stratum.…”
Section: Methodsmentioning
confidence: 99%
“…This integration began with phylogenetic studies on niche evolution (summarized in Chan et al 2011, Alvarado-Serrano and Knowles 2014; see section above and Eyres et al 2017 for an overview in birds), but the use of finer-scale genetic information together with SDMs is a much more recent innovation (Fordham et al 2014). Using information generated from genetic markers systems such as microsatellites or single nucleotide polymorphisms can add relevant insights into population structure and refine SDMs below the species level (Gonzalez et al 2011). Due to local adaptation, species-environment relationships may change among genetic groups, and data pooling at the species level may consequently lead to an overestimation of potential distribution (Oney et al 2013).…”
Section: Discussionmentioning
confidence: 99%